Preseptal and orbital cellulitis at the Philippine General Hospital - Harvey S. Uy, MD; Prospero Ma. C. Tuaño, MD (Philippine Journal of Ophthalmology)
Objective: To describe the clinical features, causative agents, management practices, and outcomes of preseptal and orbital cellulitis at a tertiary-care center in a developing country.